Pertanggungjawaban Pidana Terhadap Kontaminasi Radioaktif Cesium-137 Sebagai Jaminan Perlindungan Hak Asasi Manusia - Dialita Ayu Cendani Tuanaya; Valencia Tan A Hwa; Ulfatul Hasanah; Aisya Puteri Hutami (Unram Law Review, 2026)
Indonesia is experiencing a serious environmental problem, namely radioactive cesium-137 contamination, which is suspected to be caused by waste-processing activities carried out by PT Peter Metal Technology in Cikande, Banten. Radioactive cesium 137 has a very dangerous impact on both humans and the environment, and the negative effects of radioactive contamination can last for a very long time. The cesium-137 contamination incident indicates possible weaknesses in governmental supervision of waste-processing and sustainable environmental preservation. Thus, the issues to be discussed in this study are the responsibility of the corporation or party that caused the cesium-137 contamination to the community affected by cesium-137 and the role of the government in tackling environmental pollution to ensure the protection of the human rights of the community. This study uses a normative juridical research method with a legislative and conceptual approach. The purpose of this study is to analyze corporate responsibility for environmental pollution caused by corporate activities and to analyze the government’s responsibility for environmental pollution. The results of this study indicate that corporations must be held responsible for the occurrence of cesium 137 radioactive contamination, whereby such responsibility is limited not only to the law but also to the restoration of the impact caused by their actions. Furthermore, the government must increase its supervisory capacity, improve coordination between institutions, and ensure victims’ access to compensation and transparent public information.